Investigating Natural Killer Cell-Derived Extracellular Vesicles Using Clinically Relevant TNBC Models - Kirkby, Melanie (Université d'Ottawa / University of Ottawa, 2025)
Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer with the worst overall survival, yet viable treatment options are limited. The majority of TNBC patients rely on chemotherapy, which has several side effects and limitations. For example, chemotherapy enriches cancer stem cells (CSCs), a subpopulation of cells with a vast potential for self-renewal and cell proliferation. CSCs are highly chemoresistant, contributing to tumour recurrence and metastasis. Thus, the development of novel therapies for TNBC is a critical area of research. In this regard, natural killer (NK) cell-derived extracellular vesicles (NK-EVs) have emerged as a promising anti-cancer immunotherapeutic. As NK-EVs are derived from NK cells, they are naturally cytotoxic against cancerous cells. The objective of this project is to evaluate the efficacy of NK-EVs against TNBC. This study demonstrated that NK-EVs exhibit a short-term dose-dependent cytotoxic effect on TNBC cell viability through the activation of both apoptotic and necrotic cell death pathways. For the first time, this study demonstrated that NK-EV treatment was also effective at suppressing TNBC CSC functionality and viability. Additionally, patient-derived xenograft (PDX), a three-dimensional tumour model that originates from human patients post-surgery, were used to validate NK-EV cytotoxicity in a clinically relevant ex vivo TNBC model for the first time. Finally, in a TNBC PDX mouse model, NK-EVs administered intratumorally accumulated primarily in the tumours. Conversely, intravenous injection of NK-EVs resulted in a more systemic distribution of NK-EVs throughout the body, with the major sites of accumulation being the liver, spleen, tumour, and lungs at 24 hours. Altogether, these findings suggest that NK-EVs may have broad implications for the treatment of TNBC and, with further research, could potentially improve the prognosis of TNBC patients worldwide.
Keywords: Triple-negative breast cancer; natural killer cell; extracellular vesicle; cancer stem cell; Patient-derived xenograft